‘Mosque for Women’: History, Concept and Gender Spatial Use - Rosita Tandos (HUMANISMA : Journal of Gender Studies, 2026)
This study examines the concept of the “mosque for women” to explore women’s participation in mosques from the early Islamic period to the present and to assess how women-friendly mosque initiatives contribute to women’s empowerment. It addresses two research questions: (1) how has women’s participation in mosques evolved over time, and (2) how do contemporary women-friendly mosques support women’s empowerment and inclusive community development? The study draws on Islamic perspectives on gender relations, women’s empowerment theory, and the framework of maqāṣid al-sharīʿah. Using a qualitative approach, the research combines historical analysis, literature review, and comparative case studies of women-led and women-friendly mosques in different national contexts. Data were collected through participant observation, semi-structured interviews, and secondary document analysis conducted between 2020 and 2024, with the Grand Mosque of Istiqlal in Jakarta serving as the primary case study. The findings indicate that mosques in early Islam functioned as inclusive spaces that enabled women’s participation in religious, educational, and social activities. Contemporary women-friendly mosque initiatives, particularly at Istiqlal Mosque. This study contributes to the literature on faith-based development by demonstrating how women-friendly mosques can foster gender-inclusive participation, social inclusion, and women’s empowerment within Muslim communities.